1980
DOI: 10.1111/j.1365-2141.1980.tb03819.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Changes in Factor VIII and Platelets Preceding Deep Vein Thrombosis in Patients with Spinal Cord Injury

Abstract: The relationships between factor VIII associated activities, platelet function, and venous thrombosis were studied in 18 patients with lower limb paralysis following acute spinal cord injury (SCI). Deep vein thrombosis (DVT) was detected in 13 patients (72%). Eight of the 13 thromboses were documented between 6 and 8 d following injury while the other five episodes were noted on days 11 (two), 13, 18 and 22. The detection of thrombosis was preceded by marked increases in VIIIR:Ag and VIII:RCoF whereas VIII:C w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 24 publications
0
54
0
Order By: Relevance
“…Predisposing factors include, venous stasis due to paralysis of leg muscles associated with failure of the venous muscle pump as well as changes in the clotting mechanism. 130 Simple electrical stimulation of leg muscles in combination with low dose heparin therapy has been shown to be superior to using only heparin to prevent deep vein thrombosis (DVT) in acute SCI. 131 Although DVT is relatively rare during the chronic stage of SCI, it may be speculated that regular leg exercise by FES-LCE might be helpful in preventing DVT, but no studies have been published that have addressed this issue.…”
Section: 129mentioning
confidence: 99%
“…Predisposing factors include, venous stasis due to paralysis of leg muscles associated with failure of the venous muscle pump as well as changes in the clotting mechanism. 130 Simple electrical stimulation of leg muscles in combination with low dose heparin therapy has been shown to be superior to using only heparin to prevent deep vein thrombosis (DVT) in acute SCI. 131 Although DVT is relatively rare during the chronic stage of SCI, it may be speculated that regular leg exercise by FES-LCE might be helpful in preventing DVT, but no studies have been published that have addressed this issue.…”
Section: 129mentioning
confidence: 99%
“…3 This can cause pulmonary embolism, which is a common cause of death. 1 Various studies on DVT in acute SCI without or with prophylaxis [4][5][6][7][8][9][10][11][12][13][14][15] have reported incidence varying from 10 to 100% (Table 1a) and from 0 to 7% (Table 1b), respectively, using different diagnostic and preventive modalities. A study has been carried out in the Department of Physical Medicine & Rehabilitation and Rehabilitation Research Centre, Sawai Man Singh Medical College, Jaipur, with the aim of finding out…”
Section: Introductionmentioning
confidence: 99%
“…In the previously reported studies by Merli et at and Rossi et at DVT was reported to occur most frequently during the first 2 weeks following spinal cord injury.5, 6 Merli et at reported a 54% incid ence between days 3 through 7 and 33% days 8 through 14. 17 Rossi et al noted a 62% incidence between day 6 to 8 and a 23% incidence day 9 through 14.6 Using this data it was decided that 14 days was an adequate study period.…”
Section: Discussionmentioning
confidence: 89%